Effect of NTN and Lmx1α on the Notch Signaling Pathway during the Differentiation of Human Bone Marrow Mesenchymal Stem Cells into Dopaminergic Neuron-Like Cells. (31st July 2021) - Zhang, Jinhua; Yang, Bo; Luo, Lilin; Li, Linhui; Yang, Xuantao; Zhang, Juanjuan; Xie, Yuxin; Wang, Wanpu; Lu, Shuaiyao
Abstract : Human bone marrow mesenchymal stem cells (h-BMSCs) have the potential to differentiate into dopaminergic neuron-like cells to treat Parkinson's disease. The Notch signaling pathway has been implicated in the regulation of cell fate decisions such as differentiation of BMSCs. This study investigated changes in the expression of Notch-related genes in the differentiation of BMSCs in vitro into dopaminergic (DA) neuron-like cells. BMSCs transfected with empty lentiviral vectors served as the control group and those transfected with NTN and Lmx1 α recombinant lentiviral vectors served as the experimental group. After induction and culture of NTN and Lmx1 α -transfected h-BMSCs for 21 days, the cells exhibited features of dopaminergic neuron-like cells, which were observed by transmission and scanning electron microscopy and verified by immunofluorescence of tyrosine hydroxylase (TH) and dopamine transporter (DAT). These induced cells could secrete dopamine and had basic action potentials. Expression of the neural stem cell (NSC) markers, including octamer-binding protein ( Oct4 ), paired box gene 6 ( Pax6 ), and sex determining region Y-box 1 ( SOX1 ), increased on day 14 of induction and decreased on day 21 of induction during differentiation. The human Notch signaling pathway PCR array showed a differential expression of Notch-related genes during the differentiation of h-BMSCs into DA neuron-like cells in vitro relative to that in the control group. In conclusion, h-BMSCs overexpressing NTN and Lmx1 α can successfully be induced to differentiate into dopaminergic neuron-like cells with a neuronal phenotype exhibiting fundamental biological functions in vitro, and NTN and Lmx1 α may affect the expression of Notch-related genes during differentiation.